Clinical and angiographic success and safety comparison of coronary intravascular lithotripsy: An updated meta-analysis. (April 2022) - Sattar, Yasar; Almas, Talal; Arshad, Junaid; Zghouzi, Mohamed; Ullah, Waqas; Mir, Tanveer; Mohamed, Mohamed O.; Elgendy, Islam Y.; Aljaroudi, Wael; Prasad, Anand; Shlofmitz, Richard; Mamas, Mamas A.; et al.
Abstract: Background: Intravascular lithotripsy (IVL) can be used to assist stent deployment in severe coronary artery calcifications (CAC). Methods: Studies employing IVL for CAC lesions were included. The primary outcomes included clinical and angiographic success. The secondary outcomes, including lumen gain, maximum calcium thickness, and calcium angle at the final angiography site, minimal lumen area site, and minimal stent area site, were analyzed by the random-effects model to calculate the pooled standardized mean difference. Tertiary outcomes included safety event ratios. Results: Seven studies (760 patients) were included. The primary outcomes: pooled clinical and angiographic success event ratio parentage of IVL was 94.4% and 94.8%, respectively. On a random effect model for standard inverse variance for secondary outcomes showed: minimal lumen diameter increase with IVL was 4.68 mm (p-value < 0.0001, 95% CI 1.69–5.32); diameter decrease in the stenotic area after IVL session was −5.23 mm (95 CI –22.6–12.8). At the minimal lumen area (MLA) and final minimal stent area (MSA) sites, mean lumen area gain was 1.42 mm 2 (95% CI 1.06–1.63; p < 0.00001) and 1.34 mm 2 (95% CI 0.71–1.43; p < 0.00001), respectively. IVL reduced calcium thickness at the MLA site (SMD −0.22; 95% CI −0.40–0.04; P = 0.02); calcium angle was not affected at the MLA site. The tertiary outcomes: most common complication was major adverse cardiovascular events (n = 48/669), and least common complication was abrupt closure of the vessel (n = 1/669). Conclusions: Evidence suggests that IVL safely and effectively facilitates stent deployment with high angiographic and clinical success rates in treating severely calcified coronary lesions.